Effects on in vivo angiogenesis of extracts from astronium Urundeuva (FR. ALL.) Engl. (Anacardiaceae) - Negri, K. M.S. [UNESP]; Malafronte, N.; Certo, G.; D’Angelo, V.; Rapisarda, A.; Bauab, T. M. [UNESP]; Germanò, M. P. (My University, 2017)
Astronium urundeuva (Fr. All.) Engl. (aroeira-do-sertão) (Anacardiaceae) is an arboreal species typical of northeast brazilian savanna popularly used for its anti-inflammatory, antimicrobial, anti-ulcerogenic and healing properties. In this study the effects of A. urundeuva on in vivo angiogenesis are evaluated. Stem bark (AUS) and leaves (AUL) extracts (EtOH 70%) are investigated on zebrafish embryos and chick chorioallantoic membrane (CAM). Results of the biological screening show that AUS extracts induce a weak anti-angiogenic response in both experimental models. Conversely, AUL extracts at 25 and 50 μg/mL enhance vessel formation in zebrafish embryos submitted to the endogenous alkaline phosphatase (EAP) assay. Moreover, an increased blood vessel development and an higher level of total hemoglobin content is observed in the CAMs exposed to AUL at 80 μg/egg as compared to control. The proangiogenic effects of AUL in two in vivo models suggest its potential use as a source of new therapeutic agents able to modulate angiogenesis.
Keywords: Angiogenesis; Astronium urundeuva; Chick chorioallantoic membrane; Endogenous alkaline phosphatase staining; Haemoglobin; Zebrafish